Analisis Aktivitas Operasional dan Perencanaan Agregat pada Perusahaan Apple Inc. - Fendy Cuandra; Yulianti Yulianti; Tony Kwok; Jofen Cenedi Jongestu; Elbert Henokh Tanberius (Jurnal Bina Manajemen, 2023)
Apple Inc. is a technology company based in Cupertino, California which was founded in 1976 by Steve Jobs, Steve Wozniak, and Ronal Wayne. Apple produces hardware (hardware) and software (software). This study aims to analyze the operational activities and aggregate planning owned by the Apple company. The data collection technique used is secondary data. The research method used in this research is qualitative. Based on the analysis results obtained, that the type of process strategy used by Apple in manufacturing products is a repetitive focus strategy, even though Apple had slumped in terms of managing its supply chain, employees and inventories during the COVID-19 pandemic. However, Apple managed to rise from the slump and began designing a new strategy to deal with the COVID-19 pandemic